Revised phylogeny of extant xiphosurans (Horseshoe Crabs) - John, Akbar; Hassan, Sheikh I.; Khan Chowdhury, Ahmed Jalal; Kassim, Zaleha; Yunus, Kamaruzzaman (Springer International Publishing, 2016)
An attempt was made to revise the molecular phylogeny of extant xiphosurans (Horseshoe crabs) using universal barcode gene cytochrome oxidase C subunit 1. All four extant horseshoe crab species namely Limulus polyphemus (American horseshoe crab), Tachypleus gigas, T. tridentatus and Carcinoscorpius rotundicauda (Asian conspecifics) together with predicted ancestral lineages (insects, scorpions and common crabs) were considered for phylogram construction using distance matrix methods. Genetic distance (GD) data analysis revealed the distant genetic relatedness of L. polyphemus with Asian conspecifics. More interestingly, the monophyletic origin of Tachypleus gigas and Tachypleus tridentatus was quite evident in the phylogram which other molecular markers failed to address. Close genetic relatedness of horseshoe crabs with insects showed that they might have evolved from ancient aquatic insects. The efficiency of cytochrome oxydase C subunit 1 gene in species level identification among the horseshoe crab genome was clear in both the phylogram together with the precise identification of the differential developmental stages to the species level.